Implementation of Contextual Discovery Learning Model to Improve Scientific Literacy - Ullum, Iva Tien Nur Hidayatul; Martini, Martini (Jurnal Pijar MIPA, 2026)
Scientific literacy is an essential 21st-century competency that enables students to explain scientific phenomena, design investigations, and interpret evidence-based data. This study aims to analyze the improvement of students' scientific literacy through the application of the Discovery Learning model with a contextual approach to human respiration material. The learning context is developed through a comparative analysis of air pollution data from urban and rural areas, enabling students to examine the relationship between air quality and respiratory system disorders in a real and relevant manner. This study used a quantitative method with a one-group pretest-posttest design. The subjects were 31 eighth-grade students of SMP Negeri 1 Selorejo. The instruments used included a scientific literacy test (pretest and posttest), an observation sheet for learning implementation, and a student response questionnaire. Data analysis was carried out in stages, beginning with a normality test to determine data distribution. Because the data were not normally distributed, hypothesis testing was continued using the non-parametric Wilcoxon test. The magnitude of the increase was calculated through the N-Gain value. The results showed a significant increase in scientific literacy, as indicated by the Wilcoxon test, with an N-Gain of 0.70, which falls within the moderate category. These findings demonstrate that integrating Discovery Learning with a contextual approach grounded in urban and rural air pollution data effectively facilitates students' connections between respiratory system concepts and real-world environmental issues. Thus, this learning model contributes to strengthening scientific literacy competencies in a more meaningful and contextual way.